Pembangunan Hukum Perikanan Berkelanjutan Berbasis Kearifan Lokal - Sulaiman Sulaiman (Universitas Syiah Kuala, 2014)
Local wisdom is an impoertant fact in Indonesian society. One of wisdoms is the custom of the sea and the Panglima Laot in Aceh. it shows living legal perspective having long history in the fishery sector. This research aims to explore to which extent the extence of the wisdom having relation for the position of the leader expecially by looking the role and function focuising on the meaning of nature based on religious values. The concept and the sustainability are found based on its optical scene in looking at the wealth not only physical but also nonphysic. Sustainable Fishery Law Development Based on Local Wisdom